FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE - Rosyidah, Alif Nurul; Papilaja, Maritje Fransina; Giatamah, Zuhrah; Muhsinin, Muhsinin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Dengue fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. Based on a preliminary survey conducted at the Air Salobar Ambon Health Center in 2022, the number of patients with Dengue Fever (DHF) for the last three years showed a significant increase. The purpose of the study was to determine the factors associated with the incidence of dengue hemorrhagic fever. The research design used in this study was cross sectional. The research was conducted in December 2023 at the Air Salobar Health Center. The population is the head of the household in the working area of the Air Salobar Health Center, namely the head of the household. The sample amounted to 62 people selected using simple random sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed there was a relationship between knowledge (p value: 0.035) and breeding place (p value: 0.030) with the incidence of DHF. It is recommended that the Puskesmas can make a policy related to the supervision of dengue prevention practices and for the community to pay more attention to 3M Plus activities and the implementation of PSN-DBD independently and regularly according to standards in order to reduce the presence of mosquito larvae.Keywords: Breeding Place, Dengue Fever, Knowledge.